Temperature Control of a Hot Plate Using Microcontroller-Based PWM Technique (Global Journals of Research in Engineering, 2012)
The temperature of a hotplate used for prebaking, post baking, dehydration baking etc. changes with time. But, in baking purpose the temperature should remain constant. This work concerned with the designing a new and cost-effective microcontroller based PWM temperature controller to control the temperature of a hot plate. PWM controller has been selected because it has faster and accurate response than the conventional on-off controller. Here, the microcontroller senses the zero crossing of the line voltage and generates a pulse for every half-cycle. The width of the pulse is adjusted to change the firing angle of a TRIAC. The TRIAC is interfaced with the microcontroller circuit using an opto-coupler. The temperature of the hot plate can be increased or decreased using two push-button switches. The preset temperature will be saved in EPROM of microcontroller and displayed on an LCD display. The temperature of the hot plate is sensed by a thermocouple and fedback to the microcontroller. The microcontroller keeps the temperature constant by changing the firing angle of the TRIAC. The system has been constructed and tested successfully.
Keywords: Microcontroller; PWM controller; TRIAC; EPROM; Zero-crossing; Temperature Control